Coding semantics of handwritten annotation. (7th February 2007) - Gotze, Marcel
In this paper we discuss a concept for the description of handwritten annotations in digital documents. It is focused on the metadata but also covers the storage of the annotation data itself. For the latter SVG is used that also support the description of information about the handwritten annotation like author, type, or the text it refers to. For this data a possible use of RDF and Dublin Core is introduced that can be included within the metadata element of SVG.